The relevance of manganese in the ocean for the climatic cycles in the quaternary: Vorgelegt in der Sitzung vom 18. November 1989 - Mangini, Augusto; Eisenhauer, Anton; Walter, Peter (Springer, 1990)
The model presented here provides an explanation of the rapid response of atmospheric CO2 to increasing solar insolation. The surprising conclusion is that the oceanic (redox-)cycle of a minor element may have had a major impact on Earth's climate
Keywords: Klimaschwankung; Meer; Mangan